An esophagus cell atlas reveals dynamic rewiring during active eosinophilic esophagitis and remission - Jiarui Ding; John J. Garber; Amiko Uchida; Ariel Lefkovith; Grace T. Carter; Praveen Vimalathas; Lauren Canha; Michael Dougan; Kyle Staller; Joseph Yarze; Toni M. Delorey; Orit Rozenblatt-Rosen; et al. (Nature Communications, 2024)
Abstract Coordinated cell interactions within the esophagus maintain homeostasis, and disruption can lead to eosinophilic esophagitis (EoE), a chronic inflammatory disease with poorly understood pathogenesis. We profile 421,312 individual cells from the esophageal mucosa of 7 healthy and 15 EoE participants, revealing 60 cell subsets and functional alterations in cell states, compositions, and interactions that highlight previously unclear features of EoE. Active disease displays enrichment of ALOX15 + macrophages, PRDM16 + dendritic cells expressing the EoE risk gene ATP10A, and cycling mast cells, with concomitant reduction of TH17 cells. Ligand–receptor expression uncovers eosinophil recruitment programs, increased fibroblast interactions in disease, and IL-9+IL-4+IL-13+ TH2 and endothelial cells as potential mast cell interactors. Resolution of inflammation-associated signatures includes mast and CD4+ TRM cell contraction and cell type-specific downregulation of eosinophil chemoattractant, growth, and survival factors. These cellular alterations in EoE and remission advance our understanding of eosinophilic inflammation and opportunities for therapeutic intervention.